The Discrete Direct Deconvolution Model in the Large Eddy Simulation of Turbulence (Communications in Computational Physics, 2025)
The discrete direct deconvolution model (D3M) is developed for the large-eddy simulation (LES) of turbulence. The D3M is a discrete approximation of previousdirect deconvolution model studied by Chang et al. ["The effect of sub-filter scale dynamics in large eddy simulation of turbulence," Phys. Fluids 34, 095104 (2022)]. For thefirst type model D3M-1, the original Gaussian and Helmholtz filters are approximatedby local discrete formulation of different orders, and direct inverse of the discrete filter is applied to reconstruct the unfiltered flow field. The inverse of original Gaussianand Helmholtz filters can be also approximated by local discrete formulation, leadingto a fully local model D3M-2. Compared to traditional models including the dynamicSmagorinsky model (DSM) and the dynamic mixed model (DMM), the D3M-1 andD3M-2 exhibit much larger correlation coefficients and smaller relative errors in the a priori studies. In the a posteriori validations, both D3M-1 and D3M-2 can accuratelypredict turbulence statistics, including velocity spectra, probability density functions(PDFs) of sub-filter scale (SFS) stresses and SFS energy flux, as well as time-evolvingkinetic energy spectra, momentum thickness, and Reynolds stresses in turbulent mixing layer. D3M-1 and D3M-2 have more advantages in predicting the SFS statisticscompared to scale-similarity model (SSM), DSM, and DMM. Thus, the D3M holds potential as an effective SFS modeling approach in turbulence simulations.